Dialog Antara Filsafat dan Agama Kristen Tentang Pemahaman Rasionalitas dan Tujuan Manusia - Iswan Garamba; Ekhat Binti Patangun; Mozes Lawalata (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The relationship between philosophy and Christianity is a complex subject that has been the focus of debate for centuries. Essentially, both philosophy and religion play important roles in shaping human thought and worldview. However, there are various views and approaches to the relationship between them. On one hand, there is a traditional view among some Christians who see philosophy as something potentially dubious or even threatening to faith. They may argue that Christianity is the primary source of truth, and therefore, efforts to understand reality through the lens of philosophy may lead to deviations from religious teachings. On the other hand, philosophers often question the compatibility between philosophical intellectualism and religious belief. They may emphasize the importance of using reason and rational methods to achieve a deeper understanding of the world and truth, which may not always align with religious dogmas.History records attempts to reconcile philosophy and Christianity. Some figures such as Justin Martyr and Clement of Alexandria sought to integrate ideas from classical Greek philosophy into the framework of Christian thought. They viewed philosophy as a useful tool for defending and explaining the truth of the Christian faith to skeptics or critical thinkers. However, not all Christians embraced this approach warmly. Some believe that such efforts could cause confusion or even undermine the authenticity of Christian teachings. This could lead to conflict between those who adhere to the traditional approach and those who are more open to dialogue between philosophy and religion. Nevertheless, the debate between philosophy and Christianity continues to this day. Despite tensions between them, this interaction has also enriched our understanding of both fields. Through continuous dialogue and reflection, we can gain deeper insights into the origins, meanings, and relevance of Christian teachings in the context of the modern world.